2015
DOI: 10.1515/ohs-2015-0018
|View full text |Cite
|
Sign up to set email alerts
|

Morpholithodynamic conditions of the tip of the Hel Peninsula, the Baltic Sea

Abstract: The Hel Peninsula is a 35 km long spit that extends into water depths of almost 60 m. Unlike most sandy barriers, the distal end of the Hel Peninsula is prograding into the deep water. This affects unique conditions for the evolution of this section of the Peninsula. The aim of this study is to determine the morpholithodynamic changes on the tip of the Hel Peninsula. Shore studies were performed in 2006-2008 and 2012. Measurements included: beach profiling, determination of shoreline and dune base line positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…anom a lies in li thol ogy or depositional en viron ment and anthropogenic ac tiv ity, which might be in ter preted as di ver gence or con ver gence zones of sed i ment fluxes (Viška and Soomere, 2013;Ostrowski et al, 2014;Kovaleva et al, 2016;Krek et al, 2016). The dis tri bu tion of beach sand grain size along the Bal tic Sea coast on three spits (the Hel, Vistula and the Curonian) has been in ves ti gated in part (Žilinskas et al, 2001;Jarmalavièius and Žilinskas, 2006;Kobelyanskaya et al, 2009Kobelyanskaya et al, , 2011Zhamoida et al, 2009;Ruciñska-Zjadacz and Rudowski, 2015;Kovaleva et al, 2016;Rudowski et al, 2016;Pupienis et al, 2017). It was found that sand dif fer en ti a tion on the beach is af fected by hydro meteoro logi cal fac tors (Kobelyan skaya et al, 2011;Jarmalavièius et al, 2012a;Furmañczyk, 2013;Jarmalavièius et al, 2015;Ruciñska-Zjadacz and Rudowski, 2015;Kovaleva et al, 2016), anthropogenic ac tiv ity (Furmañczyk, 1995;Blazhchishin, 1998;Jarmalavièius and Žilinskas, 2006;Žilinskas et al, 2010;Pupienis et al, 2017) and the geo log i cal frame work (Furmañczyk and Musielak, 2015;Žilinskas et al, 2016b;Jarmalavièius et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…anom a lies in li thol ogy or depositional en viron ment and anthropogenic ac tiv ity, which might be in ter preted as di ver gence or con ver gence zones of sed i ment fluxes (Viška and Soomere, 2013;Ostrowski et al, 2014;Kovaleva et al, 2016;Krek et al, 2016). The dis tri bu tion of beach sand grain size along the Bal tic Sea coast on three spits (the Hel, Vistula and the Curonian) has been in ves ti gated in part (Žilinskas et al, 2001;Jarmalavièius and Žilinskas, 2006;Kobelyanskaya et al, 2009Kobelyanskaya et al, , 2011Zhamoida et al, 2009;Ruciñska-Zjadacz and Rudowski, 2015;Kovaleva et al, 2016;Rudowski et al, 2016;Pupienis et al, 2017). It was found that sand dif fer en ti a tion on the beach is af fected by hydro meteoro logi cal fac tors (Kobelyan skaya et al, 2011;Jarmalavièius et al, 2012a;Furmañczyk, 2013;Jarmalavièius et al, 2015;Ruciñska-Zjadacz and Rudowski, 2015;Kovaleva et al, 2016), anthropogenic ac tiv ity (Furmañczyk, 1995;Blazhchishin, 1998;Jarmalavièius and Žilinskas, 2006;Žilinskas et al, 2010;Pupienis et al, 2017) and the geo log i cal frame work (Furmañczyk and Musielak, 2015;Žilinskas et al, 2016b;Jarmalavièius et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…The dis tri bu tion of beach sand grain size along the Bal tic Sea coast on three spits (the Hel, Vistula and the Curonian) has been in ves ti gated in part (Žilinskas et al, 2001;Jarmalavièius and Žilinskas, 2006;Kobelyanskaya et al, 2009Kobelyanskaya et al, , 2011Zhamoida et al, 2009;Ruciñska-Zjadacz and Rudowski, 2015;Kovaleva et al, 2016;Rudowski et al, 2016;Pupienis et al, 2017). It was found that sand dif fer en ti a tion on the beach is af fected by hydro meteoro logi cal fac tors (Kobelyan skaya et al, 2011;Jarmalavièius et al, 2012a;Furmañczyk, 2013;Jarmalavièius et al, 2015;Ruciñska-Zjadacz and Rudowski, 2015;Kovaleva et al, 2016), anthropogenic ac tiv ity (Furmañczyk, 1995;Blazhchishin, 1998;Jarmalavièius and Žilinskas, 2006;Žilinskas et al, 2010;Pupienis et al, 2017) and the geo log i cal frame work (Furmañczyk and Musielak, 2015;Žilinskas et al, 2016b;Jarmalavièius et al, 2017a). In or der to avoid am big u ous in ter pre ta tions of long shore sed i ment transport, it is rec om mended to use sev eral dif fer ent sed i ment transport anal y sis meth ods and take into con sid er ation sta tis ti cal valid ity (Le Roux and Rojas, 2007) when as sess ing trends.…”
Section: Introductionmentioning
confidence: 99%
“…Sediments of the facies, described in detail by Rucińska-Zjadacz and Rudowski (2015), which are gene rally similar to those encountered on other beaches of the Hel Peninsula, include sands with fractions of gravel and other constituents of anthropogenic and natural origin (Wróblewski 2003;Rucińska-Zjadacz, Wróblewski 2014). …”
Section: Beach Facies 32mentioning
confidence: 90%
“…6). The upper part of the barrier is associated with the transverse barrier development due to waves and wind action (Wróblewski 2003(Wróblewski , 2009Rucińska-Zjadacz, Wróblewski 2014;Rucińska-Zjadacz, Rudowski 2015). The barrier core is built by sediments provided by longshore transport and largely discharged down the slope in the form of landslides, as well as by creeping and in suspension.…”
Section: Discussionmentioning
confidence: 99%
“…The energy of waves approaching the bay-facing shores of the Hel tip cannot dissipate due to the relief of the seabed at the tip. The edge of the coastal shoal along the western side of the tip is located about 500 m from the shore; it Rudowski 2015). Thus, the waves break close to the shore and only a small part of the energy is dissipated.…”
Section: Discussionmentioning
confidence: 99%